Welfare and Egg Production of Local Ducks Fed Diets Containing Two Probiotics in Commercial Farms - Suswoyo , I.; Rosidi (International Journal of Poultry Science, 2016)
An experiment has been conducted with the purposes to examine the effect of two kinds of probiotic on welfare and egg production of local ducks kept in commercial farms. The study was conducted in collaboration with ‘Berkah Abadi’ duck farmer group which keeps the bird under an intensive dry system. The intensive system refers to the ordinary way done by farmers in which ducks are confined to the farmer’s village with a closed fence so the ducks have no access to the outside area and the amount of feed provided could be controlled and measured. The location was in the coastal area of Tegal city as one of the most famous duck centers in Indonesia. The materials used were 15.2±1.0 months old local laying ducks which were reared by the farmer group. The study used Completely Randomized Design with probiotic and its level as the treatments. Probiotics consisted of homemade probiotic and commercial probiotic while the level comprised 0 doses (as control), 1 dose (1 ml/liter), 2 doses (2 ml/liter) and 3 doses (3 ml/liter). There were 7 treatment units which were replicated 3 times, so in total, there were 21 flocks. Each flock had 150 female ducks and one male; therefore, this study involved 3.171 ducks. Probiotics were applied each morning, mixed thoroughly in duck ration. It can be concluded that the administration of 3 ml/liter of homemade probiotic significantly increased duck welfare, egg production and egg weight; whereas the same dose of commercial probiotic significantly increased duck egg production and egg weight, but did not improve duck welfare.